Answer:
Explanation:
A). If a function 'f' is inverse of another function 'g',
Then f[g(x)] = x = g[f(x)]
In this question the given functions are,
f(x) =
and g(x) =
![(3x+1)/(x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/dx9hne0wx7zgskqdzpf9nth7wfqve3raqr.png)
Then, f[g(x)] =
![(1)/((3x+1)/(x)-3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/23zslnq1bc0tnfry5wy6urbmy1iyv9hvuu.png)
=
![(x)/(3x+1-3x)](https://img.qammunity.org/2021/formulas/mathematics/high-school/km0rsbazhmm6mzdhiuc7reciupd8gffggc.png)
= x
Similarly, g[f(x)] =
![(((3)/(x-3))+1)/((1)/(x-3) )](https://img.qammunity.org/2021/formulas/mathematics/high-school/nbgd1otzk0y13tabpmztvmfwbp260g5qg4.png)
=
![(3+x-3)/(1)](https://img.qammunity.org/2021/formulas/mathematics/high-school/cgs5jn5lsqolq74uvxmy9zieh9b8itng9u.png)
= x
Therefore, Both the functions are inverse of each other.
B). Domain of the compositions of these functions will be a set of all real numbers, (-∞, ∞)